2007
DOI: 10.1002/glia.20535
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of resident retinal microglia in the normal adult mouse

Abstract: The retina contains two distinct populations of monocyte-derived cells: perivascular cells (macrophages) and parenchymal cells (microglia), important in homeostasis, neuroinflammation, degeneration, and injury. The turnover of these cells in the retina and their repopulation in normal physiological conditions have not been clarified. Bone marrow (BM) cells from EGFP-transgenic mice were adoptively transferred into lethally irradiated normal adult C57BL/6 mice. Eight, 14, and 26 weeks later mice were sacrificed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
129
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(146 citation statements)
references
References 48 publications
13
129
4
Order By: Relevance
“…5,20 Microglia activation state was analyzed on flat mounts of the neuroretina double stained by glial fibrillary acidic protein (GFAP)/IBA-1 (Figure 7, A-H) and iNOS/IBA-1 (Figure 7, J-M). After 12 months of hyperglycemia in GK rats, activated microglial cells are identified as IBA-1-positive round amoeboid-shaped cells, located around blood vessels surrounded by GFAP-stained astrocytes ( Figure 7, B and D) compared with the control (Figure 7, A and C).…”
Section: Intravitreal Injection Of the Pkc Inhibitor In 12-month-old mentioning
confidence: 99%
“…5,20 Microglia activation state was analyzed on flat mounts of the neuroretina double stained by glial fibrillary acidic protein (GFAP)/IBA-1 (Figure 7, A-H) and iNOS/IBA-1 (Figure 7, J-M). After 12 months of hyperglycemia in GK rats, activated microglial cells are identified as IBA-1-positive round amoeboid-shaped cells, located around blood vessels surrounded by GFAP-stained astrocytes ( Figure 7, B and D) compared with the control (Figure 7, A and C).…”
Section: Intravitreal Injection Of the Pkc Inhibitor In 12-month-old mentioning
confidence: 99%
“…The hematopoietic origins of these cells suggest that they may be continuously in equilibrium with BM-derived precursors. A study using radiation and bone marrow transplantation (BMT) to create chimeric mice with green fluorescent protein-labeled monocytes suggested that the complete replenishment of retinal microglia by BM-derived monocytes takes approximately 6 months [15]. However, the radiation depletion process may accelerate microglial turnover, as another study suggested that replacement of retinal microglia by bloodborn monocytes is negligible unless retinal damage occurs [16].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the retina contains a population of bone marrowderived cells, known as microglia, which increase in number with age 51 and are constantly replenished from precursor cells. 52 In order to reach the retinal parenchyma, microglia must penetrate the BRB and clearly do so at a constant low frequency throughout life. Furthermore, recent studies have revealed a small population of professional antigen-presenting cells (dendritic cells), which express high levels of MHC Class II and reside in the retinal periphery and around the optic nerve (Figure 7).…”
Section: What Is Acaid and What Is Its Relationship To Immune Privilege?mentioning
confidence: 99%